2010
DOI: 10.1007/s13197-010-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of European squid and effects of different frozen storage temperatures on oxidative stability and fatty acid composition

Abstract: The chemical composition of European squid (Loligo vulgaris) mantles and tentacles and the lipid oxidation during frozen storage at three different temperatures (-20º, -40º and -80 °C) were investigated. The moisture, fat, protein and ash contents of tentacles were 80.72%, 1.44%, 16.16% and 1.63% while the same contents for mantle were 78.54%, 1.37%, 18.52% and 1.45% respectively. The initial free fatty acidity (FFA), peroxide (PV) and thiobarbituric acid reactive substances (TBARS) values of tentacles were 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The shift in endothermic peak temperature was possibly related to the pH of the samples during storage (Jensen and Jørgensen ). Atayeter and Ercoşkun, () reported that pH levels of squid mantles and tentacles increased during frozen storage, with pH increases in higher frozen temperatures were greater than in lower frozen temperatures. These phenomenon changes on the endothermic peak temperatures and total enthalpy of denaturation of frozen storage minced chicken and minced pork were in agreement with that reported in the literatures (Jensen and Jørgensen ; Xia et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in endothermic peak temperature was possibly related to the pH of the samples during storage (Jensen and Jørgensen ). Atayeter and Ercoşkun, () reported that pH levels of squid mantles and tentacles increased during frozen storage, with pH increases in higher frozen temperatures were greater than in lower frozen temperatures. These phenomenon changes on the endothermic peak temperatures and total enthalpy of denaturation of frozen storage minced chicken and minced pork were in agreement with that reported in the literatures (Jensen and Jørgensen ; Xia et al .…”
Section: Resultsmentioning
confidence: 99%
“…Similar changes in the carbonyl and sulfhydryl contents of proteins were observed in minced pork. The more damaging effect on protein at −4C compared to −20C was mainly due to the lipid oxidation that occurred more readily at higher storage temperatures (Atayeter and Ercoşkun, ; Hansen et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical parameters like protein quantity (Lowry et al 1951), total nitrogen (modified Kjeldahl method), total free amino acid (Misra et al 1975), Methionine content (Thimmaiah 1999), Oil extraction (Soxlet method) Acid value (Thimmaiah 1999), Free fatty acids percent (Sarvet and Ercoscun 2011), Saponification value (Horowitz 1975) Iodine value (Horowitz 1975) were estimated. In addition to this fatty acid composition, Antioxidant enzyme activities like Superoxide Dismutase (SOD) (Dhindsa et al 1981), Catalase (Dhindsa et al 1981), Ascorbate peroxidase (Nakano and Asada 1981), Free radical scavenging activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) (Mellors and Tappel 1966), Lipoxygenase (LOX) assay (Axelrod et al 1981) were measured in aged seed and compared with the control and 0 day samples for ascertaining the deterioration in the storage quality of soybean seeds.…”
Section: Biochemical Parametermentioning
confidence: 99%
“…[2,3] However, the quality characteristics and shelf life of the product are significantly different during frozen storage at different temperatures. [4,5] In addition, temperature fluctuation during frozen storage can also deteriorate the quality of the food and reduce the shelf life, which then becomes unlabeled. [6] The indicators to use in characterizing the quality of frozen aquatic products are the water-holding capacity, weight loss, color, texture properties, sulfhydryl content, and pH.…”
Section: Introductionmentioning
confidence: 99%